Perforated Jejunal Diverticulum - an Unusual Presentation - Koirala, Kamal; Khakurel, Mahesh; Barai, Reeta (Journal of Patan Academy of Health Sciences, 2015)
Jejunal diverticula are rare and usually asymptomatic. Acute complications may include haemorrhage, diverticulitis, obstruction, abscess formation and perforation. Here we report a case of 61 years lady who presented with generalized abdominal pain, vomiting and fever. There were features of acute peritonitis on examination. Exploratory laparotomy revealed a perforated jejunal diverticulum. Resection of the jejunal segment containing the perforated diverticulum and primary anastomosis was done. Histopathological examination revealed jejunal diverticulum with pinhole perforation. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13016   Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):43-45